DEVELOPMENT OF THE INDIAN VENTURE CAPITAL INDUSTRY - Chigateri, Vrata (2006)
Post liberalization, emerging markets and transition economies have become the most sought after destination for investment by venture capital firms. Governments have been undertaking radical regulatory changes in order to provide finance for the developmental phase of their economies.